2017
DOI: 10.1186/s13104-017-2492-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational factors and low back pain: a cross-sectional study of Bangladeshi female nurses

Abstract: BackgroundThe suffering from low back pain (LBP) is very common among nurses. The high prevalence rates of LBP are observed in many countries. Many back injuries are due to individual and work-related factors. Our aim is to investigate whether there is an association of occupational factors with LBP among the female nurses who are currently working in tertiary hospitals of Bangladesh.MethodsWe conducted a cross-sectional study with 229 female nurses from two selected tertiary hospitals in Bangladesh. Data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 23 publications
7
35
0
2
Order By: Relevance
“…Therefore, a total of four different measures were used to characterize LBP. The similar type of LBP measurement was done in few other studies [13,15] …”
Section: Low Back Pain Measuresmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, a total of four different measures were used to characterize LBP. The similar type of LBP measurement was done in few other studies [13,15] …”
Section: Low Back Pain Measuresmentioning
confidence: 85%
“…Due to the nature of the job, the LBP is found very common phenomenon among female garment workers, but the study concerning the prevalence and occupational factors associated with LBP is yet to an inquest especially with Bangladeshi female workers. Sanjoy et al studied the LBP among Bangladeshi nurses and found that around 31% of the nurses are having chronic LBP [13]. Moreover, the majority of literature on LBP is restricted to industrialized countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, two other studies conducted in Bangladesh found that the prevalence of LBP was 72.9% and 63% among nurses and garments workers, respectively [31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, it should be remembered  That LBP can have many non-work-related causes, • The emergence of LBP is a complex, yet unexhausted interaction of:  genetic disposition  lifestyle and nutrition  age and gender  sport and leisure behavior  stress factors from work As an example, a single study on female carers in Bangladesh is mentioned, which refers to the combination of • Insufficient support from supervisors • Overtime and • load handling Which were clearly linked to the emergence of LBP. The age, BMI and number of nurses also played a role [6]. A long-term follow-up study on back-friendly patient transfer is available from Michaelis and Hermann [7].…”
Section: State Of Researchmentioning
confidence: 99%
“…This situation is supported worldwide in many, including epidemiological, studies. For example, in Sanjoy, et al [6], 73% of 229 examined nurses reported complaints in the lumbar spine area and 32% about chronic lumbar spine diseases. A study of 2140 nurses in Portugal shows a prevalence rate of 61% for lumbar spine complaints and illnesses.…”
Section: Disc-related Diseases Of the Lumbar Spinementioning
confidence: 99%